(untitled) (Journal of Management and Business Education, 2018)
The abstract tells prospective readers what you did and what the important findings in your research were. Together with the title, it’s the advertisement of your article. Make it interesting and easily understood without reading the whole article. Avoid using jargon, uncommon abbreviations and references. You must be accurate, using the words that convey the precise meaning of your research. The abstract provides a short description of the perspective and purpose of your paper. It gives key results but minimizes experimental details. It is very important to remind that the abstract offers a short description of the interpretation/conclusion in the last sentence. The abstracts must be keep as brief as possible (200 words). In an abstract, the two whats are essential: What has been done? (purpose); what are the main findings? For example, rewarding students to enhance autonomous motivation to learn is a heavily debated topic in education studies. This research focus on the smallness of rewards. Results suggest that a small number of bonus points increases persistence in rewarded behavior, as well as persistence and performance on nonrewarded behavior.